Evolution of management of intracranial aneurysms in children: a systematic review of the modern literature - Beez, Thomas; Steiger, Hans-Jakob; Hänggi, Daniel (Journal of child neurology, 2016)
Pediatric intracranial aneurysms are rare. Management of their more common adult counterparts was profoundly influenced by recent high-quality clinical studies. The aim of this review was to aggregate the modern pediatric data published in the wake of these studies and to analyze their impact on management of aneurysms in children. A systematic PubMed search identified 135 publications published between 2000 and 2015, accounting for 573 children and 656 aneurysms. Descriptive statistical analyses revealed differences between children and adults concerning demographics and aneurysm characteristics. A significant proportion of patients were treated endovascularly, suggesting endovascular treatment has been established in the therapeutic armamentarium for pediatric aneurysms. However, these data highlight the unique nature of pediatric aneurysms, and neither this review nor generalization from adult data can replace high-quality clinical research. Multicenter registries and controlled trials are required to establish the natural history and evidence-based treatment of pediatric aneurysms.